SIMULASI APLIKASI SETOR TUNAI DAN PENGAJUAN PINJAMAN PADA PT.BANK BTPN SYARIAH MMS BEBER-CIREBON - Amelia Nurqoidah Sudrajat1; Lena Magdalena; Muhammad Hatta (Jurnal Digit, 2017)
Abstract BTPN Syariah Bank is one of the divisions of PT.Bank BTPN which has savings and lending program of medium to low-end business especially for women. One of the organizations that do the program is TIM MMS (Mobil Marketing Syariah). To conduct business processes that run quickly and precisely required information system, especially in the process of filing of the customer, and transaction processing systems menggunakkan create web-based applications. The research method used in the study is the method of data collection and system development. To input the necessary data then performed analysis and system design using tools Flowchart and UML. The programming language used is PHP and the database uses MySQL. Results from this study is a program in the form of simulations app cash deposit and loan proposals to rejuvenate TIM MMS can easily manage customer filing, loan applications, as well as computerized transaction processing, it can be concluded that this application can be used as a means to facilitate the running of business processes that run inside PT.Bank savings Bank Syariah MMS Beber. Keywords: BTPN Syariah, Deposit, Cash, Loan